Analysis of by-product formation and sugar monomerization in sugarcane bagasse pretreated at pilot plant scale: Differences between autohydrolysis, alkaline and acid pretreatment. (April 2015) - van der Pol, Edwin; Bakker, Rob; van Zeeland, Alniek; Sanchez Garcia, David; Punt, Arjen; Eggink, Gerrit
Highlights: By-product formation during pretreatment of sugarcane bagasse is analysed. Three pretreatment methods using same starting material at pilot scale are compared. Sugar monomerization efficiency identified for each pretreatment method. Large differences observed in by-product formation and sugar monomerization. Washing stage was shown to be efficient in the removal of by-products from solids. Abstract: Sugarcane bagasse is an interesting feedstock for the biobased economy since a large fraction is polymerized sugars. Autohydrolysis, alkaline and acid pretreatment conditions combined with enzyme hydrolysis were used on lignocellulose rich bagasse to acquire monomeric. By-products found after pretreatment included acetic, glycolic and coumaric acid in concentrations up to 40, 21 and 2.5 g/kg dry weight bagasse respectively. Alkaline pretreated material contained up to 45 g/kg bagasse DW of sodium. Acid and autohydrolysis pretreatment results in a furan formation of 14 g/kg and 25 g/kg DW bagasse respectively. Enzyme monomerization efficiencies of pretreated solid material after 72 h were 81% for acid pretreatment, 77% for autohydrolysis and 57% for alkaline pretreatment. Solid material was washed with superheated water to decrease the amount of by-products. Washing decreased organic acid, phenol and furan concentrations in solid material by at least 60%, without a major sugar loss.